2017
DOI: 10.1111/irv.12449
|View full text |Cite
|
Sign up to set email alerts
|

Novel multiplex assay platforms to detect influenza A hemagglutinin subtype‐specific antibody responses for high‐throughput and in‐field applications

Abstract: BackgroundDetections of influenza A subtype‐specific antibody responses are often complicated by the presence of cross‐reactive antibodies. We developed two novel multiplex platforms for antibody detection. The multiplexed magnetic fluorescence microsphere immunoassay (MAGPIX) is a high‐throughput laboratory‐based assay. Chembio Dual Path Platform (DPP) is a portable and rapid test that could be used in the field.MethodsTwelve recombinant globular head domain hemagglutinin (GH HA1) antigens from A(H1N1)pdm09 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 22 publications
6
30
0
Order By: Relevance
“…S2 samples were selected for adsorption based on MFI values (Figure ). S2 samples that showed MFIs ≥3500 against H7.NY.16.Ecto in A(H7N2) study (except one serum showed MN ≥40 and MFI = 2239) (18 out of 119) and MFIs ≥1300 against H5.Ind.05 GH in A(H5N1) study (14 out of 29) in the initial test were first adsorbed with two ectodomain rHAs (2‐Ads) from CA/09 and Perth/09 conjugated to latex beads as described previously (Figure and Table ). Selected S2 samples for 2‐Ads showed a range of MN titers against homologous viruses from 5 to 80 (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…S2 samples were selected for adsorption based on MFI values (Figure ). S2 samples that showed MFIs ≥3500 against H7.NY.16.Ecto in A(H7N2) study (except one serum showed MN ≥40 and MFI = 2239) (18 out of 119) and MFIs ≥1300 against H5.Ind.05 GH in A(H5N1) study (14 out of 29) in the initial test were first adsorbed with two ectodomain rHAs (2‐Ads) from CA/09 and Perth/09 conjugated to latex beads as described previously (Figure and Table ). Selected S2 samples for 2‐Ads showed a range of MN titers against homologous viruses from 5 to 80 (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Bio‐Plex Pro Magnetic COOH beads (Bio‐Rad, CA) were conjugated with nineteen trimeric ectodomain and/or GH HA1 antigens from influenza A(H1N1), A(H2N2), A(H3N2), A(H5N1), A(H7N2), A(H7N7), A(H7N9), A(H9N2), A(H13N9), B Victoria lineage (B/Brisbane/60/2008), B Yamagata lineage (B/Wisconsin/1/2010), and a protein A control as described previously (Table ) . The antigens were either in‐house made at CDC or obtained from International Reagent Resource and ThermoFisher Scientific (PA, USA) (Table ); the purity, trimerization, and receptor‐binding activity of in‐house made rHAs were confirmed as previously described .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations